Hypoxia-Inducible Factor (HIF)-1α Promotes Inflammation and Injury Following Aspiration-Induced Lung Injury in Mice. Issue 6 (December 2019) - Suresh, Madathilparambil V.; Balijepalli, Sanjay; Zhang, Boya; Singh, Vikas Vikram; Swamy, Samantha; Panicker, Sreehari; Dolgachev, Vladislov A.; Subramanian, Chitra; Ramakrishnan, Sadeesh K.; Thomas, Bivin; Rao, Tejeshwar C.; Delano, Matthew J.; et al.
Abstract : ABSTRACT: Acid aspiration-induced lung injury is a common disease in the intensive care unit (ICU) and acute respiratory distress syndrome (ARDS). Hypoxia-inducible factor (HIF)-1α is a major transcription factor responsible for regulating the cellular response to changes in oxygen tension. A clear understanding of the function of HIF-1α in lung inflammatory response is currently lacking. Here, we sought to determine the role of HIF-1α in type 2 alveolar epithelial cells (AEC) in the generation of the acute inflammatory response following gastric aspiration (GA). GA led to profound hypoxia at very early time points following GA. This correlated to a robust increase in HIF-1α, tissue albumin and pro-inflammatory mediators following GA in AECs. The extent of lung injury and the release of pro/anti-inflammatory cytokines were significantly reduced in HIF-1α (−/−) mice. Finally, we report that HIF-1α upregulation of the acute inflammatory response is dependent on NF-κB following GA.